Effects of nutrient loading, temperature regime and grazing pressure on nutrient limitation of periphyton in experimental ponds - Trochine, Carolina (2014)
We studied nutrient limitation of periphytic algae (henceforth periphyton) in 24 mesocosms simulating shallow lakes with two nutrient levels, enriched (with added nitrogen, N, and phosphorus, P) and unenriched (control), and three temperature scenarios, ambient, A2 from the Intergovernmental Panel on Climate Change (IPCC) and A2 + 50%. Periphyton growth (measured as chlorophyll a) was investigated four times in situ using nutrient-diffusing substrata. The effect of grazing was also manipulated using exclusion cages. We found that periphyton responded differently to nutrient addition bioassays (N and P) depending on the background nutrient concentration and warming scenario. Our results indicate that single-nutrient limitation prevailed for periphyton in our experimental temperate shallow lakes. The responses were season sensitive. Periphyton in the unenriched mesocosms were P-limited in early summer in the ambient and A2 scenarios, N-limited in late summer in these two climate scenarios, not nutrient-limited in autumn and P-limited in spring in all climate scenarios. Periphyton in the A2 + 50% scenario showed a positive response to N and P added together in early summer. In contrast, periphyton in the enriched mesocosms showed no clear nutrient limitation, except for short-term periods of P limitation in the warmer systems. Grazers did not affect the quantitative response of periphyton to nutrient addition, and the concentrations of P and N as well as mean monthly temperature were the main environmental factors driving P or N limitation. We conclude that warming in low-productivity lakes affects the seasonality of N limitation and changes the single-nutrient limitation of periphyton into NP co-limitation. This last observation suggests that warming reduces the sensitivity of temperate shallow lakes to bottom-up perturbations.